Transformasi Kurikulum Madrasah Strategi Integrasi Kecerdasan Spritual Dalam Kurikulum Fiqih di Madrasah Tsanawiyah - Agus Samsul Nahar; Deden Kurnia Adam; Euis Komala; Badruddin; Qiqi Zakiah Yulianti (CBJIS: Cross-Border Journal of Islamic Studies, 2024)
The background to the problem is the importance of transforming the Madrasah curriculum into spiritual intelligence strategies in the Fiqh curriculum at Madrasah Tsanawiyah. To answer the challenges of the times and advances in the world of education, the research methodology used is a descriptive qualitative method and a literary bibliography in the form of books. and internet. The research objective is to find out about implementation. obstacles and outcomes. The first implementation is to carry out direction (commanding), guidance (directing) and communication (communication). Second, implementation (actuating) is nothing but an effort to make planning a reality, through various directions and motivations so that each student can carry out activities optimally in accordance with their roles, duties and responsibilities. Spiritual intelligence strategy is a person's ability to surrender to God. and enjoy every reality and give meaning to worship in every behavior and activity through steps and thoughts that are natural towards the whole human being (hanif) and have a monotheistic (integralistic) thought pattern. Spiritual intelligence is the perfection of the development of the mind (such as intelligence, sharpness of mind), while "Spiritual" is psychological (spiritual, inner). Obstacles are circumstances that can cause implementation to be disrupted and not carried out well. The results achieved are setting life goals. The first step to increasing spiritual intelligence is by setting life goals. Understanding one's inner values. A person's inner values can shape beliefs, direct behavior and choices, and at the same time influence feelings about aqidah, morals and spiritual intelligence, ensuring that all elements work in balance.